(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study explored the learning dynamics associated with Integrated Development Environments (IDEs) and Command-Line Interfaces (CLIs) for teaching and learning java programming language in the Department of Computer Science at the College of Education and Legal Studies, Ringim. The study evaluates the effectiveness of different programming tools (IDEs and CLIs) in enhancing the learning experience of Java programming students. It seeks to understand how these tools impact learners’ confidence, skill development, and overall programming proficiency. The results revealed distinct advantages and challenges associated with each environment, underscoring the importance of context and learner preferences in selecting the appropriate tool for Java programming education. The study provides valuable recommendations for educators on optimizing programming instruction to better meet the needs of diverse learners.